2015
DOI: 10.1007/s10311-015-0496-4
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride in the environment: sources, distribution and defluoridation

Abstract: Fluoride is one of the most widespread groundwater pollutant. More than 200 million people, from 25 nations, are suffering from fluorosis. This review presents an overview of fluoride distribution in groundwaters, and defluoridation techniques. Adsorption is the most common technique; however, the efficiency, sorbate disposal and continuous supply of efficient sorbates are still problematic. Membrane processes are quite efficient but not economical for developing communities. This article therefore highlights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
67
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(75 citation statements)
references
References 112 publications
2
67
0
6
Order By: Relevance
“…methods were conducted in Dugda district, Oromia reign. This study revealed the coverage of community fluoride filtered water utilization at the time of this study was 56.3% this utilization was comparable or nearly similar with studies done at the northern part of the Ethiopian Rift Valley that revealed the consumption of fluoride-free water dropped to less than 60% (9). But, lower as compared to studies As it is obtained from key informant interview result and community survey result 211(52%) of the interviewed H/H had orthodox religion followers in the area and they believe that bone char filters were interrupting the pasting day of their religion so that it is not acceptable by most of the local community in the area due to religious reason.…”
Section: Discussionsupporting
confidence: 83%
“…methods were conducted in Dugda district, Oromia reign. This study revealed the coverage of community fluoride filtered water utilization at the time of this study was 56.3% this utilization was comparable or nearly similar with studies done at the northern part of the Ethiopian Rift Valley that revealed the consumption of fluoride-free water dropped to less than 60% (9). But, lower as compared to studies As it is obtained from key informant interview result and community survey result 211(52%) of the interviewed H/H had orthodox religion followers in the area and they believe that bone char filters were interrupting the pasting day of their religion so that it is not acceptable by most of the local community in the area due to religious reason.…”
Section: Discussionsupporting
confidence: 83%
“…Fluoride (F), the compound of fluorine (the most active element in the natural environment), exists very extensively in the living environment, for instance, groundwater, soil, food, industrial pollutant, drugs, and dental hygiene products [1,2]. As we all know that F is necessary in lots of physiological activities.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been known for long time that extreme intake of fluoride, at concentrations higher than 1 mg/L, can lead to severe dental and skeletal fluorosis as shown in Fig. 1 (Vithanage and Bhattacharya 2015). Dental and skeletal fluorosis, a disease can cause mottling of the teeth due to the excess fluoride and calcification of ligaments.…”
Section: Introductionmentioning
confidence: 99%